2016
DOI: 10.1002/app.43392
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization efficiency of bulk‐fill dental resin composites with different curing modes

Abstract: The aim of this study was to investigate the effect of four different curing modes on the polymerization efficiency of eight bulk‐fill composites. Five specimens for each material were prepared for Vickers hardness measurements. The measurements were performed at 0 and 2 or 4 mm from the top of the surface of the specimens 24 h after photopolymerization. Statistical analysis was performed with one‐way analysis of variance and Tukey post hoc tests at a level of significance of a = 0.05 where a is the the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…However, it has been reported that filler size of composite resins may influence attenuation of radiation through the materials. More specifically, Dionysopoulos et al found that different filler composition may affect photopolymerization of composite resins in deeper layers. This phenomenon may be explained by the fact that the size of fillers of the dental composite materials affects their translucency.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that filler size of composite resins may influence attenuation of radiation through the materials. More specifically, Dionysopoulos et al found that different filler composition may affect photopolymerization of composite resins in deeper layers. This phenomenon may be explained by the fact that the size of fillers of the dental composite materials affects their translucency.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to overcome these disadvantages and simplify the time-consuming incremental technique of composite restorations, a new category of composite restorative materials has been introduced the socalled "bulk fill" composite resins. Bulk fill composite resins are assumed to be curable to a thickness of 4-5 mm [13], develop lower polymerization shrinkage stresses [14] and present higher light transmission properties due to reduction of light scattering at the filler-matrix interface by either decreasing the filler amount [5] or increasing the filler size [15]. To achieve this extended depth of cure bulk fill composite resins have acquired certain modifications in their composition in order to increase penetration of visible light through the materials such as increased filler size [15] and novel photoinitiators [16].…”
Section: Editorialmentioning
confidence: 99%
“…13 Various methods such as incremental layering technique, softstart polymerization modes, guided shrinkage direction, application of liners under the restoration, low-shrinkage materials and increased filler content in the composition of resins have been proposed for this reason. [14][15][16][17][18] Incremental restorative technique of composite resins has been recommended for large and deep posterior cavities in order to reduce the deleterious effects of stress contraction. 15,[19][20][21][22] Nevertheless, this technique increases the treatment time, the risk of incorporating voids or contaminants between composite layers and failure in bonding between the increments.…”
Section: Introductionmentioning
confidence: 99%